219k views
0 votes
Rewrite the following parametric equations in rectangular form.

x=e^3t
y=e^-t

1 Answer

5 votes
To solve this problem you must apply the proccedure shown below:
1. You have the following parametric equations given in the problem above:
x=e^3t
y=e^-t
2. Therefore, you must solve fot et in the second equation, as below:
y=e^-t
y=1/e^t
e^t=1/y
3.Substitute into the first equation:
x=e^3t
x=(e^t)^3
x=(1/y)^3
x=1/y^3 (y>0)
The answer is: x=1/y^3 (y>0)
User Nicolas Garnier
by
6.6k points